Supply Chain Information System Model for New Breed of Graduate Management for Higher Education in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim to develop supply chain information system model for new breed of graduate management for higher education in Thailand and an evaluation of the model . Samples are ten experts in the field of information system and supply chain. Ten experts are selected by purposive sampling method. The obtained data are analysed using mean and standard deviation. The research result demonstrates the model consists of five elements namely main components, Supplier, University ( Manufacturer) , Education Customers and Consumers. The data analysed by using arithmetic mean and standard deviation supply chain information system model for new breed of graduate management for higher education in Thailand using Back-Box technique. The results from ten experts have evaluated the model and commented that the developed model showed high suitability.